The Influence of Leadership Style, Individual Characteristics, and Incentives on Employee Performance at PT. Bank Perkreditan Rakyat Nusantara Bona Pasogit 20 Delitua - Elisabeth Simangunsong; Efri Elsridayani Purba; Kristina Bangun (Cita konsultindo, 2026)
This research discusses how the influence of leadership style, individual characteristics and incentive provision at PT. BPR NBP 20 Delitua. This data was obtained through a survey of questionnaires distributed to 45 (Forty Five) employees at PT. BPR NBP 20 Delitua. The sampling technique used was saturated sampling or census, while the data analysis used was multiple linear regression conducted using SPSS 25 software. The research method used in this study is a quantitative analysis method. Based on the results of the analysis using SPSS 25 software, it is known that Y = 1.419 + 0.100X1 + 0.292X2 + 0.446X3. Leadership style has a significant effect on employee performance, t count (2.886) > t table (1.682). There is a significant influence between individual characteristics and employee performance. With t count (3.883) > t table (1.682). There is a significant influence between incentive provision and employee performance. With the calculated t value (5.596) > t table (1.682). The coefficient of determination (R2) = 74,3% indicates the magnitude of the influence of leadership style, individual characteristics and incentives on employee performance, while the remaining 25,7% is influenced by other factors not included in this study. From the results of the F test, it is known that the calculated F is 39.410 > F table of 2.83 and the significant value of F is 0.000 < α (0.05) so that H0 is rejected and H1 is accepted, meaning that simultaneously the variables of leadership style, individual characteristics and incentives have a positive and significant effect on employee performance at PT. BPR NBP 20 Delitua.